1984
DOI: 10.1139/b84-077
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae in a southern California desert: ecological implications

Abstract: Perennial plants of 19 families were surveyed for colonization by vesicular–arbuscular mycorrhizal (VAM) fungi at four sites in the Anza–Borrego Desert State Park, California, an area characterized as arid to extremely arid. Soils at all sites were very low in phosphorus and nitrogen and had a coarse sandy texture. The sites were distinct in the floristic composition of their vegetation. All plants (38 species) were colonized by VAM fungi (six species). The distribution of the VAM mycoflora was not random. Sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 25 publications
1
35
1
2
Order By: Relevance
“…This study showed a trend of species diversity of AMF being negatively correlated with plant species diversity along the successional gradient. Data from a temperate region showed that AMF diversity tended to increase with successional rank in an old field succession (Johnson et al 1991), while fungal diversity was relatively uniform in a desert ecosystem despite the diversity in the plant community (Bethlenfalvay et al 1984). Increase in AMF species richness was accompanied by an increase in plant diversity and ecosystem productivity in simulated macrocosms of temperate ecosystems (van der Heijden et al 1998).…”
Section: Number Of Viable Sporesmentioning
confidence: 99%
“…This study showed a trend of species diversity of AMF being negatively correlated with plant species diversity along the successional gradient. Data from a temperate region showed that AMF diversity tended to increase with successional rank in an old field succession (Johnson et al 1991), while fungal diversity was relatively uniform in a desert ecosystem despite the diversity in the plant community (Bethlenfalvay et al 1984). Increase in AMF species richness was accompanied by an increase in plant diversity and ecosystem productivity in simulated macrocosms of temperate ecosystems (van der Heijden et al 1998).…”
Section: Number Of Viable Sporesmentioning
confidence: 99%
“…Many desert plants are known to be mycorrhizal (Rose, 1981;Bethlenfalvay et al, 1984;Pond et al, 1984;Bloss, 1985;Bloss and Walker, 1987;Cui and Nobel, 1992), including columnar cacti (Rose, 1981), although no studies have determined the relative dependence on mycorrhizae. We sought to evaluate whether vesicular-arbuscular mycorrhizae (VAM) fungi have a role in the primary establishment of cactus species under mesquite trees.…”
Section: Introductionmentioning
confidence: 99%
“…Seedling recruitment and species diversity decline in the absence of AMF, especially during secondary succession (Gange et al 1990;Grime et al 1987). AMF fungal benefits to host plants potentially are great in nutrient poor or deficient soils or in extreme environments where the symbiosis acts to overcome plant stress (Allen and Allen 1984;Bethlenfalvay et al 1984;Miller 1979;Molina et al 1978). In stressful environments, higher plants that are mycorrhizal are likely to experience a competitive advantage over those that are non-mycorrhizal (Doerr et al 1984;Filler 1985).…”
Section: Downy Brome and Soil Symbiontsmentioning
confidence: 99%